Terahertz transparency of optically opaque metallic films - Song, Zhengyong (2014)
Here we present an alternative approach to design a freestanding transparent conducting device for wide-angle and polarization-insensitive incidence of electromagnetic waves at terahertz frequencies. It is realized by depositing periodic metallic patches on top and bottom of the subwavelength metallic mesh. Based on the numerical computations, the deposited metallic patches can suppress the reflection and enhance the transmission. The high transmission of the designed system is attributed to the impedance matching to the vacuum. This design of a transparent conducting device can be useful in applications, such as optoelectronic electrodes and micro-electronic displays, where both high electrical conductivity and high optical transmittance are desirable.